Introduce Climate-Sensitive Building Codes to Reduce Urban Density And Encourage Sustainable Urban Growth - Iqbal, Tasnova; Mahtab, Muhammad Shadman (MAJ - Malaysia Architectural Journal, 2025)
The study focused on assessing the attributes of traditional urban houses, in dense cities such as Dhaka, that reduced urban density and catered to sustainable urban growth, to introduce climate-sensitive building codes. Dhaka being the capital of Bangladesh is expanding rapidly with minimal space for urban green and community interactions. Dhaka building code does not fully solve the issue of sustainability and density unlike the fine grain traditional buildings of old Dhaka with its climate-sensitive courtyard houses. The Rajdhani Unnayan Kartripakkha (RAJUK) approves building permits based on floor area ratio, maximum ground coverage, setback, fire safety, parking provisions, room dimensions, specific requirements on a case-to-case basis and based on the area and its special features; but the climate-responsive steps in building codes is completely missing till now unlike those practiced in traditional urban houses. This study aimed at assessing the factors of climate-sensitive traditional urban houses which minimized urban density and catered to sustainable urban growth to introduce climate-sensitive building codes to reduce urban density and encourage sustainable urban growth. The research methodology adopted a mixed method approach. Attributes that contribute to reducing urban density and encouraging sustainable growth were identified through literature review and evaluated by field observation. The case studies selected, for qualitative research, are a multistoried traditional urban residence in Panam City and a modern residential apartment in Dhaka which was designed maintaining building codes and acts. The quantitative method included measuring the climate-sensitive aspect of courtyards through Rhino and Grasshopper; and assessing the perceptual density of the street, proposed with modern courtyard buildings, through questionnaires. Key findings indicated that many climate-sensitive features from traditional urban dwellings can be incorporated into new building codes to reduce urban density. Finally, the study proposed possible climate-sensitive building codes aimed at reducing urban density and encouraging sustainable urban growth.